Impact of Farmers’ Use of Information Technology to Improve Agricultural Marketing Extension Services in Wasit Governorate, Iraq - Shehata, Gaber Ahmed Bassyouni; El-Habal, Abo Zaid M.; El-Sharbatly, Souzan I.; Abdulrazzaq, Ali H. (Advances in Social Sciences Research Journal, 2022)
The research presented in the study of the impact of farmers’ use of Information Technology (IT) in the field of improving agricultural marketing extension services indicates the small number of researches that dealt with this topic as one of the mechanisms of agricultural extension work, hence the importance of theoretical and applied research. The agricultural sector in Iraq seeks to reach advanced stages in agriculture in general, which must keep pace with the development of agricultural production methods that have developed greatly over the past years. Therefore, farmers in Iraq, with the diversity of agricultural fields that they practice, are in dire need of correct and integrated marketing information about crops. Which are produced and the marketing methods and tools that suit each crop, and in particular the main strategic important crops that represent the main food for the Iraqi people, such as grains, vegetables and . In order to modernize agriculture, all kinds of agricultural technological progress must be put into practice, which is in line with the concept of guidance in general in conscious influence in the minds of farmers through the transfer of information and knowledge to help them make a sound decision in the use of modern technology. The main objective of this research is to identify the impact of farmers' use of information technology (IT) to improve agricultural marketing extension services in Wasit Governorate, Iraq, and its relationship to some social and economic characteristics of farmers in the research area. Based on the result of the research, the model of estimating the value of the multiple regression coefficients between the studied independent variables and the dependent variable, the impact of farmers' use of information technology (IT) in the field of agricultural marketing includes fifteen independent variables, and the significance of the model as a whole has been clarified based on the ratio (P), which amounted to about (15,530), in addition to that these variables contribute to explaining 72% ​​of the changes occurring in the variable The effect of farmers’ use of information technology (IT) in the field of agricultural marketing services based on the coefficient of determination (R2), and it was clear from this model the significance of the effect of each of the independent variables, namely: the age of the farmers surveyed, agricultural experience, the number of respondents’ family members, and the number of workers The respondents' farm, the type of agricultural land holding, the means of transportation for marketing agricultural crops, and the respondents' knowledge level.